Regulation of Microtubule Dynamics by Bim1 and Bik1, the Budding Yeast Members of the EB1 and CLIP-170 Families of Plus-End Tracking Proteins - Blake-Hodek, Kristina A. (The American Society for Cell Biology, 2010)
Microtubule dynamics are regulated by plus-end tracking proteins (+TIPs), which bind microtubule ends and influence their polymerization properties. In addition to binding microtubules, most +TIPs physically associate with other +TIPs, creating a complex web of interactions. To fully understand how +TIPs regulate microtubule dynamics, it is essential to know the intrinsic biochemical activities of each +TIP and how +TIP interactions affect these activities. Here, we describe the activities of Bim1 and Bik1, two +TIP proteins from budding yeast and members of the EB1 and CLIP-170 families, respectively. We find that purified Bim1 and Bik1 form homodimers that interact with each other to form a tetramer. Bim1 binds along the microtubule lattice but with highest affinity for the microtubule end; however, Bik1 requires Bim1 for localization to the microtubule lattice and end. In vitro microtubule polymerization assays show that Bim1 promotes microtubule assembly, primarily by decreasing the frequency of catastrophes. In contrast, Bik1 inhibits microtubule assembly by slowing growth and, consequently, promoting catastrophes. Interestingly, the Bim1-Bik1 complex affects microtubule dynamics in much the same way as Bim1 alone. These studies reveal new activities for EB1 and CLIP-170 family members and demonstrate how interactions between two +TIP proteins influence their activities.